Transform hate speech in education from gender perspectives. Conceptions of Chilean teachers through a case study - Marolla-Gajardo, Jesús; Castellví-Mata, Jordi (Frontiers in Education, 2023)
The research presented is positioned under the issue of hate speech prevalent in society, particularly its emergence in schools. In recent years, we have witnessed the presence of a phenomenon that is not new; however, it poses challenges to the teaching and learning processes for educators. Specifically, feminist movements and those advocating for diversity and nonconformity have triggered a strong response filled with violent and discriminatory messages and actions. To obtain some answers to this challenge, a case study was conducted with 6 teachers from various schools in Chile. Semi-structured interviews were carried out to explore, from their perspectives, aspects such as the origins of hate speech, the possibilities and proposals that teachers have for creating counter-narratives against hate, the effects of hate messages from gender perspectives in their teaching practices, and finally, the processes carried out with students. Among the main conclusions, it can be mentioned that there is a violent disruption that deepens gender inequalities, a situation that is becoming normalized and is of great concern for educators. Teachers express that they lack the tools and competencies to address these problems, other than continuing with the treatment of official content.